How to build a framework to establish a patient research partner network in rheumatology research: a report of a 2-year implementation project - Maarten de Wit; Oliver Distler; Cosimo Bruni; Anna-Maria Hoffmann-Vold; Muriel Elhai; Rucsandra Dobrota; Adrian Ciurea; Caroline Ospelt; Raphael Micheroli; Dania Diem; Stefan Dudli; Kristina Buerki; et al. (RMD Open)
Background Patient research partners (PRPs) are people living with a relevant disease who actively contribute to research. Their contribution is beneficial for any research project. Although the inclusion of PRPs in rheumatology research is increasingly recommended, its practical implementation, particularly in translational research, remains limited . Enhancing PRP engagement requires a clear understanding of the necessary steps.Objective This study aims to show steps to achieve successful collaboration between PRPs and researchers in clinical and transitional research in rheumatology.Methods We established a PRP network by following five main steps: setting up infrastructure, recruitment, training, PRP involvement at an early stage, and ongoing support. We adhered to overall principles of openness, feedback, and regular evaluations to create a respectful and collaborative environment. The initiative was qualitatively assessed via an online questionnaire developed by each six researchers and PRPs.Results Communicating our initiative at laboratory open days and to patient associations has enabled to create a network of 66 PRPs. A match-making tool was introduced to allocate interested PRPs with a project request. This led to PRP involvement in 15 projects, including 9 in translational research. Two PRP-coordinators provided support including glossaries and educational courses .Conclusion Our initiative outlines five essential steps for establishing PRP collaboration in rheumatology research, including translational research. This approach benefited both PRPs and researchers and might serve as a guide for other centres.